Deterministic coupling of epitaxial semiconductor quantum dots to hyperbolic metamaterial - Jang, Y. D.; Baek, J. S.; Devaraj, V.; Kim, M. D.; Song, J. D.; Wang, Y.; Zhang, X.; Lee, D. (OPTICAL SOC AMER, 2018)
Hyperbolic metamaterial (HMM) can enhance the radiative recombination rate of a near-field coupled emitter due to its large photonic density of states (PDOS). Thus far, this enhancement has only been demonstrated qualitatively on account of the difficulties to achieve an equal emitter-HMM distance as well as the same polarization for all emitters. Here, we report on the deterministic coupling of epitaxially grown quantum dots (QDs) with HMM, for which a quantitative investigation of the rate enhancement is possible. Advantages of epitaxial QDs over other emitters to investigate HMM coupling include a precise QD-HMM distance, the same polarization direction, and single-exponential decay of photoluminescence. In order to isolate metal-related effects, we have fixed the thickness of the silver (Ag) layer and have varied only that of the germanium (Ge) layer in the HMM to investigate the effect of the PDOS, which depends on the dispersion relation, which in turn depends on the thickness ratio. The recombination rate enhancement, as measured by lifetime reduction, varied from 2.2 to 4.2, depending on the thickness ratio of Ag and Ge in the HMM. These findings match well with simulation results, clearly supporting the role of HMM in the rate enhancement. The coupling of high-quality epitaxial QDs with HMM, demonstrated here for the first time, to the best of our knowledge, may bring about diverse future applications. (C) 2018 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
Keywords: WETTING LAYER; SILVER FILMS; ULTRA-SMOOTH; CAVITIES